Pengaruh Lembar Kerja Siswa Menggunakan Software Prezi Terhadap Minat Belajar Siswa Mata Pelajaran PPKn Kelas VIII Smpn 30 Muaro Jambi - Musdalifah, Musdalifah; Irwan, Irwan; Simaremare, Tohap Pandapotan (Civic Education Perspective Journal, 2022)
This research was conducted with the aim of knowing the effect of student worksheets using Prezi software on interest in learning class VIII in chapter VI, this research was conducted at SMPN 30 Muaro Jambi in the even semester of the 2021/2022 academic year. The results of the calculation of the increase in the NGain score show that the average Ngain score for the experimental class is 6.3980 which is included in the High category while the average Ngain score for the control class is -2.3717 which is included in the Low category. with the reported data normally distributed and uniform. Then based on the "Independent Sample Test" results table above it is known that the value of Sig. (two sides) is 0.003 <0.05, so it can be concluded that there is a significant (significant) difference in effect between the use of student boards using the Prezi software on the learning benefits of class VIII students of SMPN 30 Muaro Jambi in the 2021/2022 academic year, therefore it can be it was concluded that there was an effect of using student worksheets using Prezi software on the learning interest of class VIII students of SMPN 30 Muaro Jambi for the 2021/2022 academic year. From the results of the research above, it is better for teachers to do teaching when using learning media, so that students can be interested and enthusiastic in participating in the learning process and can easily understand the teaching material presented. For schools, it is better to be able to provide facilities that can assist teachers in applying learning media because of course it will also provide benefits for schools, namely in the form of knowledge, insight, literature review repertoire regarding Prezi learning media to attract student learning interest.